Taking or not taking medications: psychiatric treatment perceptions in patients diagnosed with bipolar disorder. (24th September 2014) - Vargas‐Huicochea, I.; Huicochea, L.; Berlanga, C.; Fresán, A.
Summary What is known and objective Bipolar disorder is a common and disabling condition. Although its negative impact may be limited in some way by the use of different treatment options, lack of adherence to psychiatric treatment is still an obstacle to overcome. Because there are many factors involved in non‐adherence to treatment, in this study, we sought to examine the subjective aspect of this phenomenon. We analysed perceptions of both the disease and the treatment in a group of patients with bipolar disorder. Methods We incorporated a qualitative design that included 50 outpatients diagnosed with bipolar disorder type 1. Through semi‐structured interviews, we explored patients' perceptions of bipolarity and psychiatric medication management. Results and discussion The participants reported the use of medications as one of the most troubling aspects of having bipolar disorder. The fear of becoming addicted to psychiatric drugs was repeatedly mentioned among the patients as an argument for abandoning treatment. The main expectation of treatment was to achieve stable mood, but the patients considered that drugs were not the only way to be euthymic. What is new and conclusions The patients expressed ambivalence between the need to take medication to remain stable and the fear of negative consequences of using psychiatric drugs. Personal beliefs and environmental influences seem to determine each individual's final choice of whether to maintain or discontinue treatment; so, in everyday clinical practice, it would be necessary to discuss perceptions of the disease with patients and their families.